Clinical Belongingness and its Relationship with Clinical Self-Efficacy among Nursing Students: A Descriptive Correlational Study - Sima Pourteimour; Hossein Jamshidi; Naser Parizad (Kashan University of Medical Sciences, 2021)
Background: Clinical self-efficacy (CSE) plays a pivotal role in safe and quality nursing care delivery. Clinical Belongingness (CB) is a major factor in the clinical practice of nursing students. Objective: This study aimed to assess CSE and CB and their relationship among nursing students. Methods: This descriptive, correlational study was conducted in 2019 in the Faculty of Nursing and Midwifery of Urmia University of Medical Sciences, Urmia, Iran. Participants were 216 eligible 3rd- and 4th-year nursing students. Data were collected using a demographic questionnaire, the Belongingness Scale-Clinical Placement Experience, and the Self-Efficacy in Clinical Performance Questionnaire. The Pearson correlation analysis, the independent-sample t-test, the one-way analysis of variance, and the linear regression analysis were performed for the data analysis. Results: The total mean scores of CSE and CB were, respectively, 134.02 ± 20.62 and 121 ± 16.79, indicating moderate CSE and high CB. CB had significant positive correlation with CSE and was a significant predictor of it (P < 0.05). Conclusion: Nursing students have high CB and moderate CSE, and their CB is a significant positive predictor of their CSE. University authorities are recommended to develop clear strategies to improve nursing students' CSE through improving their CB.